1990
DOI: 10.1164/ajrccm/141.1.169
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnosis of Mild Emphysema: Correlation of Computed Tomography and Pathology Scores

Abstract: Early and accurate diagnosis of emphysema is said to be invaluable for identification of clinically silent and mild emphysema. Recently, computed tomography (CT) has been much advocated for its efficacy in detailed diagnosis of emphysema, and the results have been compared with the pathology grade of emphysema in resected lung specimens. To assess the ability of high resolution CT scan in detecting and grading mild emphysema, we correlated the high resolution CT scan with the pathology grade of emphysema and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
98
0
3

Year Published

1997
1997
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 270 publications
(107 citation statements)
references
References 1 publication
6
98
0
3
Order By: Relevance
“…HRCT imaging detects early emphysema by identifying pulmonary tissue with radiologic attenuation below a predetermined threshold, findings that roughly correlate with a low DL CO and pathologic evidence of emphysema (74)(75)(76)(77)(78)(79)(80). Although several studies have shown that a significant proportion of asymptomatic smokers have HRCT evidence of emphysema (78,(81)(82)(83), early HRCT findings of ''emphysema'' are not proven to be correlated directly with lung destruction (84)(85)(86)(87)(88)(89)(90). Hyperpolarized gas diffusion-weighted magnetic resonance imaging has also been used to identify emphysema, with a correlation of elevated levels of the apparent diffusion coefficient with decreased DL CO (91).…”
Section: Early Detection Of Lung Destructionmentioning
confidence: 99%
“…HRCT imaging detects early emphysema by identifying pulmonary tissue with radiologic attenuation below a predetermined threshold, findings that roughly correlate with a low DL CO and pathologic evidence of emphysema (74)(75)(76)(77)(78)(79)(80). Although several studies have shown that a significant proportion of asymptomatic smokers have HRCT evidence of emphysema (78,(81)(82)(83), early HRCT findings of ''emphysema'' are not proven to be correlated directly with lung destruction (84)(85)(86)(87)(88)(89)(90). Hyperpolarized gas diffusion-weighted magnetic resonance imaging has also been used to identify emphysema, with a correlation of elevated levels of the apparent diffusion coefficient with decreased DL CO (91).…”
Section: Early Detection Of Lung Destructionmentioning
confidence: 99%
“…Scans were viewed using a window level of -600 HU and width of 1,500 HU, and were independently examined by two chest radiologists for the presence of areas of low attenuation and vascular disruption. The severity of emphysema was scored on a nonparametric scale from 0 (no emphysema) to 100 using the picture-grading method of THURLBECK et al [6] adapted for CT [7]. According to this method, a score of f5 is consistent with trace emphysema, a score of 10-30 indicates mild emphysema, a score of .30-50 moderate emphysema and a score of .50 severe emphysema.…”
Section: Computed Tomographymentioning
confidence: 99%
“…Thin-section computed tomography (CT) has been used to quantify emphysema by detecting low attenuation areas (LAA), and the role of CT in diagnosing emphysema, including subclinical emphysema (2,3), has been well established (4)(5)(6)(7)(8)(9). However, airflow limitation evaluated by forced expiratory volume in 1 s (FEV 1 ) does not necessarily have a good correlation with the severity of emphysema as evaluated by CT (10), because small airway disease appears to contribute more significantly to the airflow limitation in COPD (1,(11)(12)(13)(14).…”
mentioning
confidence: 99%